Experimental investigation on surface characterization of chemical treated Natural fiber composite - chandrasekeran, prasanna; C, Ramesh (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
In this research work removal of lignin and hemicelluloses for untreated coir fiber reinforced composites was accomplished by suitable chemical treatment namely new method at optimum fiber loading such as 25% and 30%. To avoid the problem of untreated coir fiber, chemical treatment was done. Final treated fiber extraction process was gone through new method. It results in treated cellulose composite at 25% and 30% lignin and hemicelluloses was found to be decreased was revealed in Fourier transform infrared spectroscopy analysis, it shows defibrillation, de-polymerization in treated composite was revealed in scanning electron microscopy analysis, and shows high oxygen content percentage than carbon content percentage about 22.06% which demonstrates removal of lignin in treated composite, was revealed in element detection analysis.. The main objective was accomplished by the removal of lignin and hemicelluloses of natural fiber through suitable chemical treatment and at optimum fiber loading